Knowledge on First Aid Management of Injury among Workers at Honda Service Centre - Nakarmi , Simran; Kandel, Bhawana (Solukhumbu Multiple Campus Research Journal, 2025)
First aid is the initial, emergency care given to anyone with a minor or serious disease or injury, with the goal of preserving life, preventing the condition from getting worst or promoting recovery. The objective of the study was to identify the Knowledge regarding First Aid Management of Injuries among Workers at Honda Service Centers at Kathmandu. A descriptive cross-sectional study design was conducted among 60 Workers of Honda Service Centers. Non probability purposive sampling technique was used to collect the data. A semi-structured interview schedule was developed to measure the research variable regarding Knowledge regarding First Aid Management of Injuries among Workers at Honda Service Centers. The study was conducted at the Honda Service Center among 60 automobile workers. The result of the study showed that more than half of the respondents 33(55%) had a low level of Knowledge, 11 (18.3%) had a moderate knowledge level and 16 (26.7%) had a higher level of Knowledge. There was no statistically significant association between the socio-demographic variables with level of education, duration of work. The study concluded that more than half of the respondents had a low level of Knowledge on first aid management, and only a few of them had moderate and high levels of knowledge. A larger study could be done among a larger population of different automobile companies for generalization.